Recruitment processes among foreign-born engineers and scientists in Silicon valley - Alarcon, Rafael (1999)
This article examines the processes by which Indian and Mexican engineers and scientists find employment in the high-technology companies of Silicon Valley. The quantitative and qualitative data used in this study come from the U.S. Census (1990 Public Use Microdata Samples) and from 20 case studies of Indian and Mexican professionals. There is a much larger concentration of foreign-born engineers and scientists in Silicon Valley than in other high-technology regions of the United States. These immigrants play a crucial role in this knowledge-based industry because they have much higher levels of education than their native counterparts. The recruitment and hiring of these workers underscore the importance of the operation of social networks. They either worked for subsidiaries of U.S. companies located abroad or were students at U.S. universities. Some others entered the country as children of immigrant families or are "high-tech braceros," that is, temporary workers holding nonimmigrant visas. - Reproduced
Keywords: Scientists; Engineers; Recruitment; Immigration